Mechanism of Permanganate Biosorption by Fermentation Biowaste - Namgyu Kim; Sang-Hoon Lee; Hanui Yang; Donghee Park (Adsorption Science & Technology)
Biosorptive treatment of industrial wastewater contaminated with heavy metals has been recognized as one of the most effective green tools, competing with traditional physical/chemical treatment processes. This study delves into the detailed investigation of the biosorbent prepared from fermentation biowaste, particularly focusing on the mechanism behind permanganate (Mn(VII)) removal. Various parameters including pH, biosorbent dosage, initial concentration, and temperature were examined. Among these factors, solution pH emerged as the most crucial in removing Mn(VII) using the biosorbent. The significant removal of Mn(VII) was attributed to both reduction and adsorption, as confirmed by X-ray photoelectron spectroscopy. Depending on the experimental conditions, the removal of Mn(VII) was influenced not only by simple adsorption but also by oxidation-reduction and precipitation processes. This study not only advances our understanding of biosorptive treatment but also highlights the promising potential of fermentation biowaste-based biosorbents for effective Mn(VII) removal.